Flux-assisted single crystal growth and heteroepitaxy of perovskite-type mixed-metal borohydrides1. Issue 13 (7th April 2015) - Schouwink, Pascal; Ramel, Adrien; Giannini, Enrico; Černý, Radovan
<x xml:space="preserve">Abstract</x> Single crystals of mixed-metal perovskite-type borohydride KCa(BH4)3 are prepared by using an easily generalized flux melting procedure based on eutectic borohydride systems.